STUDY ON THE EFFECT OF RESIDUAL STRESS FIELD ON THE CRACK GROWTH RATE OF CIVIL WELDED PLATE - CHEN YangLiu; SONG Xin; BAI ChengZheng; SHENG HongWei; ZHANG JiaZhen (Jixie qiangdu)
In order to reduce the cost of fatigue crack growth test and shorten the research period of welding process on new aircraft siding structure,this paper uses Abaqus finite element software to simulate welding residual stress field by using predefined temperature field method.The stress intensity factor values of crack tip are obtained by finite element simulation.Based on the structural characteristics of large welded plate,the Pairs formula was used to predict the crack propagation rate of welded plate.Based on this model,the fatigue crack growth rate of specimens with different stress ratio and welding process was studied.It is found that the effective stress ratio increases with the residual stress,but the effect decreases with the increase of the stress ratio.The trend of the effective stress ratio is similar to that of the residual stress distribution.The welding residual stress increases the crack growth rate of the welded structure.The feasibility of the proposed method is verified by comparison with the experimental results.